Impact of Salt Stress on Plants: Innovative Mitigation Strategies for Stress Alleviatin - Fathi, Amin; Shiade, Seyede Roghie Ghadirnezhad; Shohani, Fariba; Saleem, Ammara; Zulfiqar, Asma; Riaz, Ameel; Fazeli, Arash (Natl Information Documentation Cent, Acad Scientific Research & Technology, 2026)
P LANT growth and development are hindered by salinity stress, which poses a serious threat to crops. The substantial influence this environmental problem has on different phases of plant growth, including photosynthesis, mineral absorption, seed germination, and finally grain formation and yield, is one noteworthy feature of the problem. Numerous factors, including inhibition of biological process, enzyme activity, hormonal balance, and the use of seed reserves, are influenced by salt stress on seed germination. This review highlights the impact of salt stress on different plant growth stages, particularly focusing on reduced grain development and yield during the reproductive stage. It also discusses emerging strategies like using plant growth regulators, genetic engineering, rhizobacteria, and nanotechnology to mitigate salt stress. These strategies aim to enhance plant resilience to salinity, address specific physiological impacts like ion toxicity, and potentially improve crop yield and quality in saline environment.
Keywords: Plant growth; Germination; Yield; Salt stress; Photosynthesis